Redesigning the Borobudur chair to sustain local creative industries: introducing to wangun concept - Widayat, Rahmanu (International Journal of Engineering and Technology, 2020)
Redesigning the already existed thing is a common practice in the world of design. This study objectively conducted to produce a fresh new look and commercially bargaining product of furniture in addition to pursue current aesthetic needs. This study focuses on reconstructing the Borobudur chair, a typical form of chair inspired from the 8th century Borobudur temple reliefs, which theoretically does not follow modern art. This proposes a traditional conceptual approach called wangun (beauty) inspired by the wisdom of local Javanese culture, which is termed as Ngowahi Rupa (the change of form). Ngowahi Rupa does not change the 'inner structure' of an object, the changes occur only at the 'outer structure' level. There were two distinctive chairs being redesigned in this study, the first type of chair can accommodate one person only, and the other accommodates three people. Both types of chairs constitute of a complete structure of chair such as the legs, seat stands, and backrests, which in the sense of wangun conceptually termed telu-teluning atunggal. The Ngowahi Rupa furniture making process not only demands visual aspects, but also the concept of the creative industry. The concept was applied in redesigning the Borobudur chair that synergically in accordance with the rapidly developed creative industries in Indonesia. The results of redesigning the old-type of chair objectively contribute to the advance of current furniture industry and trend, both in Indonesia and abroad, in addition to maintaining the excellence of the creative industry with regard to the economic concern.Â Â